Effect of Mg addition on the crystallization kinetics of Zn-Al-Cu alloys - Krupinski, Mariusz; Labisz, Krzysztof; Jonda, Ewa (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
The main issue was to determine the effect of Mg addition on the crystallization kinetics and microstructure of Zn-10Al-1Cu alloy. The effectiveness of magnesium modification was decided on the basis of microstructure morphology studies and changes occurring in the cooling curves of the investigated alloys. To describe the phenomena that occur in the material during solidification under various conditions caused by a change in the chemical composition as a result of the appliance of modifiers, it was decided to use methods of thermal derivative analysis, allowing to effectively and accurately describe the crystallization kinetics of the tested materials. The scientific goal of the presented work was to attempt to answer current research questions, including: how will the addition of magnesium affect the kinetics of crystallization of the examined alloys? What will be the relationship between the changes in the derivative curve and the related microstructure? Also the comparison to the material without modification is a part of this work. The addition of Mg has caused a shift of the solidification temperature values of phases and eutectics and eutectoid transformation to lower temperature values, as well as has changed the morphology of the occurring eutectic α’+η.